Une gloire singulière. Pour une meilleure réception de Rimbaud au Japon - Yoshikazu Nakaji (Seminario di filologia francese, 2021)
It is in the 1930s, thanks to the translation of A Season in Hell by the critic Hideo Kobayashi and the Poems by the poet Chûya Nakahara, that Rimbaud begins to be anchored in the Japanese culture as one of the most prestigious foreign poets. The translations of famous people helped Rimbaud's reception, but it is also true that their fame was enhanced by the fact that they were Rimbaud's translators. However, their translations reveal linguistic problems to such an extent that they could be described as a showcase of bad translations. The glory of the poet as well as that of the translators generated by the translation is a singular glory based on misunderstanding. The true understanding of Rimbaud would only begin when, with the bad imprint of these translations eradicated, a new translator would provide a linguistically accurate and appropriate translation to the language of the time.